Patient preferences for biologicals in psoriasis: top priority of safety for cardiovascular patients - Schaarschmidt, Marthe-Lisa; Herr, Raphael; Schmieder, Astrid; Sonntag, Diana; Goerdt, Sergij (PLOS ONE, 2015)
Patients with psoriasis are often affected by comorbidities, which largely influence treatment decisions. Here we performed conjoint analysis to assess the impact of comorbidities on preferences of patients with moderate-to-severe psoriasis for outcome (probability of 50% and 90% improvement, time until response, sustainability of success, probability of mild and severe adverse events (AE), probability of ACR 20 response) and process attributes (treatment location, frequency, duration and delivery method) of biologicals. The influence of comorbidities on Relative Importance Scores (RIS) was determined with analysis of variance and multivariate regression. Among the 200 participants completing the study, 22.5% suffered from psoriatic arthritis, 31.5% from arterial hypertension, 15% from cardiovascular disease (myocardial infarction, stroke, coronary artery disease, and/or arterial occlusive disease), 14.5% from diabetes, 11% from hyperlipidemia, 26% from chronic bronchitis or asthma and 12.5% from depression. Participants with psoriatic arthritis attached greater importance to ACR 20 response (RIS = 10.3 vs. 5.0, p<0.001; β = 0.278, p<0.001) and sustainability (RIS = 5.8 vs. 5.0, p = 0.032) but less value to time until response (RIS = 3.4 vs. 4.8, p = 0.045) than those without arthritis. Participants with arterial hypertension were particularly interested in a low risk of mild AE (RIS 9.7 vs. 12.1; p = 0.033) and a short treatment duration (RIS = 8.0 vs. 9.6, p = 0.002). Those with cardiovascular disease worried more about mild AE (RIS = 12.8 vs. 10, p = 0.027; β = 0.170, p = 0.027) and severe AE (RIS = 23.2 vs. 16.2, p = 0.001; β = 0.203, p = 0.007) but cared less about time until response (β = -0.189, p = 0.013), treatment location (β = -0.153, p = 0.049), frequency (β = -0.20, p = 0.008) and delivery method (β = -0.175, p = 0.023) than others. Patients’ concerns should be addressed in-depth when prescribing biologicals to comorbid patients, keeping in mind that TNF antagonists may favourably influence cardiovascular risk.